A correction algorithm for rotor-induced airflow and flight attitude changes during three-dimensional wind speed measurements made from a rotary unoccupied aerial vehicle - Y. Yang; Y. Zhang; T. Han; C. Xie; Y. Liu; Y. Huang; J. Zhou; H. Sun; D. Zhao; K. Zhang; S.-M. Li (Atmospheric Measurement Techniques)
A hexacopter unoccupied aerial vehicle (UAV) was fitted with a three-dimensional sonic anemometer to measure three-dimensional wind speed. To obtain accurate results for three-dimensional wind speeds, we developed an algorithm to correct biases caused by the rotor-induced airflow disturbance, UAV movement, and attitude changes in the three-dimensional wind measurements. The wind measurement platform was built based on a custom-designed integration kit that couples seamlessly to the UAV, equipped with a payload and the sonic anemometer. Based on an accurate digital model of the integrated UAV–payload–anemometer platform, computational fluid dynamics (CFD) simulations were performed to quantify the wind speed disturbances caused by the rotation of the UAV's rotor on the anemometer during the UAV's steady flight under headwind, tailwind, and crosswind conditions. Through analysis of the simulated data, regression equations were developed to predict the wind speed disturbance, and a correction algorithm for rotor disturbances, motions, and attitude changes was developed. To validate the correction algorithm, we conducted a comparison study in which the integrated UAV flew around a meteorological tower from which three-dimensional wind measurements were made at multiple altitudes. Comparison between the corrected UAV wind data and those from the meteorological tower demonstrated excellent agreement. The corrections result in significant reductions in wind speed bias caused mostly by the rotors, along with notable changes in the dominant wind direction and wind speed in the original data. The algorithm enables reliable and accurate wind speed measurements in the atmospheric boundary layer made from rotorcraft UAVs.